Reform of the Zemstvo Representation: Development and Adjustment of P. A. Stolypin Project in 1906—1907. - A. A. Sorokin (Научный диалог, 2020)
The article is devoted to the little-studied issue of the development and adjustment of the reform provisions of the zemstvo representation of P.A. Stolypin in 1906—1907. The main programmatic requirements of liberal circles to change the procedure for elections to zemstvo assemblies, developed by zemstvo assemblies, zemstvo congresses, as well as local committees of the Special Meeting on the needs of the agricultural industry. For the first time, on the materials of the Russian State Historical Archive, the evolution of the provisions of the draft and their criticism in the Council of Ministers, as well as at the Congress of the United Nobility in 1907, is shown. It is emphasized that the development of the reform was a consequence of the Manifesto adopted in 1903 and 1904 and the decree on the need to transform local government and self-government. The author states that initially P. A. Stolypin sought to increase the share of representatives from cities and commercial and industrialists in zemstvo assemblies, however, at the insistence of the Council of Ministers, he was forced to retain the majority for landowners. The criticism of the united nobility in relation to the reform in connection with the expansion of the circle of voters and the organization of elections at the beginning of the non-class is highlighted in the article. It is concluded that the transformation of elections into zemstvo assemblies, planned by P. A. Stolypin was aimed at involving broad strata of the population in the representative institutions of local self-government at the expense of an unclassified beginning and the organization of elections based on a tax qualification.